Effect of Berberine Phytosome on reproductive, dermatologic, and metabolic characteristics in women with polycystic ovary syndrome: a controlled, randomized, multi-centric, open-label clinical trial - Di Pierro, Francesco; Sultana, Ruqqia; Eusaph, Amna Zia; Abrar, Saida; Bugti, Mahroo; Afridi, Fauzia; Farooq, Umer; Iqtadar, Somia; Ghauri, Fareeha; Makhduma, Syeda; Nourin, Shazia; Kanwal, Ayesha; et al. (Frontiers in Pharmacology, 2023)
Background: Berberine is a poorly absorbed natural alkaloid widely used as nutraceutical to counteract diarrhoea and to lower cholesterol and hyperglycaemia. It has also been reported to reduce signs and symptoms of polycystic ovary syndrome (PCOS).Objective: To explore, through a multi-centric, randomized, controlled and prospective study, the possible role played by a form berberine that is more easily absorbed (Berberine Phytosome®, BP) in 130 Pakistani women with a diagnosis of PCOS and fertility problems due to menstrual and ovary abnormalities.Results: Ninety days of supplementation with BP, administered at 550 mg x2/die, determined (i) resumption of regular menstruation in about 70% of women (versus 16% in the control group; p<0.0001), (ii) normalization of the ovaries anatomy in more than 60% of women (versus 13% in the control group; p<0.0001), (iii) acne improvement in 50% of women (versus 16% in the control group; p=0.0409) and (iv) hirsutism reduction in 14% of women (versus 0% in the control group; p=0.0152). The metabolic and the hormonal profiles of the women in the two groups did not significantly differentiate at the end of the study.BP was well-tolerated and no specific side-effects were registered. Respectively after one, two and eight years of trying, three women supplemented with BP became and are currently pregnant.Our study showed the positive effects of BP supplementation in women with PCOS and confirmed the high safety profile of this nutraceutical.